The tertierization of manufacturing industry in the "new economy" - Andrea Szalavetz (Transformation, Integration and Globalization Economic Research (TIGER), 2003)
In the early transformation years, the incorporation of the transforming economies in the global structure of manufacturing was characterized by a partial geographical separation of production related service activities from production (physical processing activities). Part of the physical processing tasks has been assigned to the newly acquired and modernized enterprises in the transforming countries. These companies have become single-functional production facilities within their multinational owners' organization. With rapid factor costs increases however, the initial competitiveness of simple processing activities based on low labor costs has more or less eroded in transforming economies. Both local subsidiaries and their parent companies recognized, that the only way to compensate for the declining profitability of certain manufacturing activities is to redefine the value chain of local subsidiaries, of the single-functional production facilities, and include services into the range of activities carried out by these subsidiaries. This process followed with some time lag the accelerating tertierization of manufacturing in advanced economies, which happened as an outcome of manufacturing companies' strategic response to the challenges of the 'new economy'. This paper examines the theoretical concept of and some empirical evidence for the tertierization of manufacturing as a 'new economy' phenomenon. Revisiting her past hypotheses concerning the 'new economy' driven shift in the distribution of various types of world trade, the author analyzes the methodological difficulties of the analysis of statistical data on international trade in services, i.e. the difficulties to quantify the volume and the value of intra-firm services. Based on the results of field investigations at a sample of representatives of the Hungarian machinery industry (MNCs' local subsidiaries) the paper contrasts the Hungarian experience with the theoretical theses. Thereby it tries to answer the question, whether information technology revolution has facilitated that economic actors outside the center of the world economy increase the role of intangible elements in their value creation activities, diversify their corporate activity portfolio, and improve in that way their position within their owners' multinational organization.
Keywords: 330; Dienstleistung; Industrie; Diversifikation; Ungarn; New Economy